Correction: Xie et al. Distributed Attitude Synchronization for Spacecraft Formation Flying via Event-Triggered Control. Appl. Sci. 2021, 11, 6299 - Xiong Xie; Tao Sheng; Liang He (Applied Sciences, 2022)
We, the authors, wish to make the following corrections to our paper [...]